Simulering som læringsmetode kan bidra til økt sykepleiefaglig handlingskompetanse i rurale strøk - Eva Tharaldsteen; Inger Skoglund (Septentrio Academic Publishing, 2015)
Simulation as a learning method can recreate reality. The method has three aspects to it, consisting of building a scenario, making the students familiar with it, and debriefing them after the scenario is played out. This learning method enables both students and healthcare professionals to train various acute patient situations, while staying in a safe environment and without harming the patient. Simulation can in a harmless way uncover knowledge shortcomings and uncertainty, which is not easily recognized because of the lack of training opportunity. This being because of the long timespan between each emergency occurring in reality. The article is based on experiences and reflections that we as teachers have acquired, through using simulation as a learning method for acute nursing students coming from different rural and remote municipalities in Finnmark. Working in remote areas requires adequate depth and breadth of knowledge, in relation to the local community's needs for health care services.